Occurrence of Multidrug Resistant Methicillin-Resistant Staphylococcus aureus and Methicillin-Susceptibility Staphylococcus aureus in Chon Buri Province - Nimrat, Subuntith; Puengsurin, Duangchewan; Vuthiphandchai, Verapong (Science Essence Journal, 2019)
บทคัดย่อ การศึกษาครั้งนี้มีจุดประสงค์เพื่อศึกษาความไวและแบบแผนการดื้อยาต้านจุลชีพของ Methicillin-resistant Staphylococcus aureus (MRSA) จำนวน 103 ไอโซเลท และ Methicillin-susceptibility Staphylococcus aureus (MSSA) จำนวน 136 ไอโซเลท ที่แยกได้จากผู้ป่วยในโรงพยาบาลชลบุรี และโรงพยาบาลสมเด็จพระบรมราชเทวี ณ ศรีราชา จังหวัดชลบุรี พบว่า พบว่า MSSA ทุกไอโซเลทมีความไวต่อยาต้านจุลชีพ Oxacillin, Cefoxitin, Cefuroxime และ Vancomycin และเกือบทุกไอโซเลทดื้อต่อ Penicillin G และ Ampicillin ยกเว้น MSSA ที่แยกได้จากโรงพยาบาลชลบุรี คิดเป็น 2.88% เท่ากัน ส่วน MRSA ทุกไอโซเลทที่แยกได้จากทั้ง 2 โรงพยาบาล มีความไวต่อ Vancomycin และดื้อต่อ Penicillin G, Ampicillin, Oxacillin และ Cefoxitin ส่วนแบบแผนการดื้อยาหลายชนิดของ MRSA ที่แยกได้จากโรงพยาบาลสมเด็จพระบรมราชเทวี ณ ศรีราชา และโรงพยาบาลชลบุรี พบว่ามีแบบแผนการดื้อยาต้านจุลชีพมากกว่า 6 ชนิดขึ้นไปมากที่สุด คิดเป็น 94.74% และ 97.62% ตามลำดับ และ MSSA มีแบบแผนการดื้อต่อยาต้านจุลชีพ 3 ชนิดมากที่สุด คิดเป็น 71.87% และ 60.58% ตามลำดับ จากการศึกษาครั้งนี้ชี้ให้เห็นว่าทั้ง MRSA และ MSSA ที่คัดแยกมาจากจังหวัดชลบุรีมีการดื้อต่อยาต้านจุลชีพหลายชนิด โดยเฉพาะอย่างยิ่ง MRSA ดื้อต่อยาต้านจุลชีพในกลุ่มเบต้าแลคแตมมากที่สุด คำสำคัญ: Methicillin-resistant Staphylococcus aureus (MRSA)Methicillin-susceptibility Staphylococcus aureus (MSSA) ความไวต่อยาต้านจุลชีพ การดื้อยาปฏิชีวนะหลายชนิด ABSTRACT The aim of this study was to investigate the antimicrobial susceptibility and pattern of multidrug resistance of methicillin-resistant Staphylococcus aureus (MRSA; 103 isolates) and methicillin-susceptibility Staphylococcus aureus (MSSA; 136 isolates) recovered from the patients in Chon Buri Hospital and Queen Savang Vadhana Memorial Hospital in Chon Buri Province. All isolates of MSSA were susceptible to oxacillin, cefoxitin, cefuroxime and vancomycin. Almost all MSSA isolates were resistant to penicillin G and ampicillin, except 2.88% MSSA isolated from Chon Buri Hospital. All MRSA isolates recovered from both hospitals exhibited susceptibility to vancomycin and were resistant to penicillin G, ampicillin, oxacillin and cefoxitin. In case of antimicrobial resistant pattern of S. sureus isolated from Queen Savang Vadhana Memorial Hospital and Chon Buri Hospital, MRSA showed the highest resistance to more than 6 types of antimicrobial agents (94.74% and 97.62%, respectively) while MSSA presented the highest resistance to 3 types of those agents (71.87% and 60.58%, respectively). This finding indicated that both MRSA and MSSA collected from hospitals in Chon Buri Province were resistant to multiple antimicrobial agents, particularly, beta-lactam antibiotics resistance of MRSA. Keywords: Methicillin-resistant Staphylococcus aureus (MRSA), Methicillin-susceptibility Staphylococcus aureus (MSSA), Antimicrobial susceptibility, Multidrug resistant